Single inhaler extrafine triple therapy in uncontrolled asthma (TRIMARAN and TRIGGER): two double-blind, parallel-group, randomised, controlled phase 3 trials. Issue 10210 (9th November 2019) - Virchow, Johann Christian; Kuna, Piotr; Paggiaro, Pierluigi; Papi, Alberto; Singh, Dave; Corre, Sandrine; Zuccaro, Florence; Vele, Andrea; Kots, Maxim; Georges, George; Petruzzelli, Stefano; Canonica, Giorgio Walter
Summary: Background: To date, no studies have assessed the efficacy of single-inhaler triple therapy in asthma. Here we report on two studies that compared the single-inhaler extrafine combination of beclometasone dipropionate (BDP; inhaled corticosteroid), formoterol fumarate (FF; long-acting β2 agonist), and glycopyrronium (G; long-acting muscarinic antagonist) with the combination of BDP with FF. Methods: Two parallel-group, double-blind, randomised, active-controlled, phase 3 trials (Triple in Asthma With Uncontrolled Patients on Medium Strength of ICS + LABA [TRIMARAN] and Triple in Asthma High Strength Versus ICS/LABA HS and Tiotropium [TRIGGER]) recruited patients from 171 sites across 16 countries (TRIMARAN), and from 221 sites across 17 countries (TRIGGER). The sites were a mixture of secondary and tertiary care centres and specialised investigation units. Eligible patients were adults (aged 18–75 years) with uncontrolled asthma, a history of one or more exacerbations in the previous year, and previously treated with inhaled corticosteroid (TRIMARAN: medium dose; TRIGGER: high dose) plus a long-acting β2 agonist. Enrolled patients were initially treated with BDP/FF (TRIMARAN: 100 μg BDP and 6 μg FF; TRIGGER: 200 μg BDP and 6 μg FF) for 2 weeks, then randomly assigned to treatment using an interactive response technology system with a balanced block randomisation scheme stratified by country. Patients, investigators, site staff, and sponsor staff were masked to BDP/FF/G and BDP/FF assignment. In TRIMARAN, patients were randomly assigned (1:1) to 52 weeks of BDP/FF/G (100 μg BDP, 6 μg FF, and 10 μg G) or BDP/FF (100 μg BDP and 6 μg FF), two inhalations twice daily. In TRIGGER, patients were randomly assigned (2:2:1) to 52 weeks of BDP/FF/G (200 μg BDP, 6 μg FF, and 10 μg G) or BDP/FF (200 BDP and 6 μg FF), both two inhalations twice daily, or open-label BDP/FF (200 μg BDP and 6 μg FF) two inhalations twice daily plus tiotropium 2·5 μg two inhalations once daily. Coprimary endpoints for both trials (BDP/FF/G vs BDP/FF) were pre-dose forced expiratory volume in 1 s (FEV1 ) at week 26 and rate of moderate and severe exacerbations over 52 weeks. Safety was assessed in all patients who received at least one dose of study treatment. These trials were registered with ClinicalTrials.gov, NCT02676076 (TRIMARAN), NCT02676089 (TRIGGER). Findings: Between Feb 17, 2016, and May 17, 2018, 1155 patients in TRIMARAN were given BDP/FF/G (n=579) or BDP/FF (n=576). Between April 6, 2016, and May 28, 2018, 1437 patients in TRIGGER were given BDP/FF/G (n=573), BDP/FF (n=576), or BDP/FF plus tiotropium (n=288). Compared with the BDP/FF group, week 26 predose FEV1 improved in the BDP/FF/G group by 57 mL (95% CI 15–99; p=0·0080) in TRIMARAN and by 73 mL (26–120; p=0·0025) in TRIGGER, with reductions in the rate of moderate and severe exacerbations of 15% (rate ratio 0·85, 95% CI 0·73–0·99; p=0·033) in TRIMARAN and 12% (0·88, 0·75–1·03; p=0·11) in TRIGGER. Four patients had treatment-related serious adverse events, one in TRIMARAN in the BDP/FF/G group and three in TRIGGER—one in the BDP/FF/G and two in the BDP/FF group. Three patients in the BDP/FF/G group in TRIMARAN and two patients in TRIGGER—one in the BDP/FF/G group and one in the BDP/FF group—had adverse events leading to death. None of the deaths were considered as related to treatment. Interpretation: In uncontrolled asthma, addition of a long-acting muscarinic antagonist to inhaled corticosteroid plus long-acting β2 -agonist therapy improves lung function and reduces exacerbations. Funding: Chiesi Farmaceutici.